On the effects of modified lane configuration due to construction works on bridge loading - Marcel Nowak; Oliver Fischer (Acta Polytechnica CTU Proceedings, 2022)
Construction works are frequently recurring events within highway networks, temporarily altering the characteristics of the traffic flow and hence of the bridge loading process. Consequently, highway bridge superstructures usually carrying unidirectional traffic might have to face modified configurations, with possibly altered lane widths and transverse lane positions, or even an increased number of lanes and the occurrence of bidirectional traffic flow. While usually covering only short periods compared to the average service life of a bridge, such scenarios might represent extreme loading situations, potentially dominating the traffic loading process. Therefore, their consideration and accurate modeling in the course of traffic load assessment and development of object-specific traffic load models are of utmost importance. The presented study analyzes data from bridge monitoring along federal highway A92 in Southern Germany. The data covers standard and different modified lane configurations due to construction works. Besides analyzing the effects on traffic flow characteristics and resulting occurrence rates of multiple truck presence on the bridge, the consequences for load effects and their extreme value behavior are also evaluated. The findings support verification of related code background works and can serve as base and guidance for future research efforts on bridge load modeling in this context.